Efficacy and safety of tolvaptan for pediatric patients with congestive heart failure. Multicenter survey in the working group of the Japanese Society of PEdiatric Circulation and Hemodynamics (J-SPECH). (15th February 2016) - Higashi, Kouji; Murakami, Tomoaki; Ishikawa, Yuichi; Itoi, Toshiyuki; Ohuchi, Hideo; Kodama, Yoshihiko; Honda, Takashi; Masutani, Satoshi; Yamazawa, Hirokuni; Senzaki, Hideaki; Ishikawa, Shiro
Abstract: Background: Tolvaptan, a vasopressin V2-receptor antagonist, has been reported to improve congestion in adult patients with heart failure. However, it has not been fully clarified whether tolvaptan is also effective and safe for pediatric patients as well as adult. Methods: This trial was a multicenter, retrospective, observational study, and was led by the Japanese Society of PEdiatric Circulation and Hemodynamics (J-SPECH). Thirty-four pediatric patients who received tolvaptan to treat congestive heart failure were enrolled in this study. Results: An increment in the urinary volume and decrease in the body weight from baseline were significant at day 1 (+ 106.7 ± 241.5%, p = 0.008 and − 2.30 ± 4.17%, p = 0.01), day 3 (+ 113.5 ± 261.9%, p = 0.02 and − 2.30 ± 4.17%, p = 0.01), week 1 (+ 56.3 ± 163.5%, p = 0.01 and − 1.55 ± 4.09%, p = 0.03) and month 1 (+ 91.1 ± 171.6%, p = 0.01 and − 2.95 ± 5.98, p = 0.03). The significant predictive factors in responders, who was defined as patients who achieved an increase in the urinary volume at day 1, were older age (p = 0.03), larger body weight before exacerbation (p = 0.04), higher weight at one day before the first administration of tolvaptan (p = 0.03), higher aspartate aminotransferase levels (p = 0.03) and higher urinary osmolality levels (p = 0.03). A logistic regression analysis showed that the urinary osmolality was the only significant predictive factor for responders to tolvaptan. Adverse drug reactions were observed in 7 patients (20.6%). Six patients had thirst and a dry month, and 1 had a mild increase in the alanine aminotransferase and aspartate aminotransferase. Conclusion: Tolvaptan can be effectively and safely administered in pediatric patients. Because the kidneys in neonates and infants are resistant to arginine vasopressin, the efficacy of tolvaptan may be less effective compared to older children.